2021
DOI: 10.1108/qram-11-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

“Measuring up”: a systematic literature review of performance measurement in Australia and New Zealand local government

Abstract: Purpose Measurement practices have long been considered vital for informing the management of performance in organisations. Their application to local governments is a more recent, yet multi-decade phenomenon facilitated by New Public Management trends. This paper aims to review the landscape of publications that discuss performance measurement (PM) practices in Australian and New Zealand local government contexts and identify implications for future research. Design/methodology/approach A systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 99 publications
(151 reference statements)
1
6
0
Order By: Relevance
“…We applied this method by collecting and analysing scholarly literature referring to sustainability materiality research. In doing so, we followed the research methods of prior SLRs (Dienes et al , 2016; Hinze and Sump, 2019; Johnsson et al , 2021; Mio et al , 2020b; Roberts et al , 2021; Veltri and Silvestri, 2020; Widyawati, 2020). Thus, we developed a research protocol consisting of methodological steps regarding the research plan, search strategy for conducting the review, content analysis of the extant literature and compilation of the findings.…”
Section: Methodsmentioning
confidence: 99%
“…We applied this method by collecting and analysing scholarly literature referring to sustainability materiality research. In doing so, we followed the research methods of prior SLRs (Dienes et al , 2016; Hinze and Sump, 2019; Johnsson et al , 2021; Mio et al , 2020b; Roberts et al , 2021; Veltri and Silvestri, 2020; Widyawati, 2020). Thus, we developed a research protocol consisting of methodological steps regarding the research plan, search strategy for conducting the review, content analysis of the extant literature and compilation of the findings.…”
Section: Methodsmentioning
confidence: 99%
“…When it comes to the use of PM for improvements, it seems that a choice must be made between using the PM to develop and improve the local operations or using it for comparability on a macro-level (Johnsson et al , 2021; Zidarov et al , 2017). For example, Johnsson et al (2021) showed that models of working with quality and continuous improvements in performance resulted in improvements on a local level, but when used for benchmarking between organisations, the results instead emphasised the lack of flexibility in the models and difficulties in using them for improvements. In line with this, Lewis (2015) concludes that PMs are mainly used at the meso-level, by managers, and not by politicians at the macro-level nor at the micro-level of operations.…”
Section: Theoretical Frame Of Referencementioning
confidence: 99%
“…In their study, it was reported on a macro-level that the PMs for benchmarking purposes worked and were perceived as useful and valid, but became too general and difficult to use on a micro-level. This indicates that comparing measures for the same activities can be used for benchmarking purposes, but when the perspective is moved to the organisational level, measures may lose relevance for the operative level (Zidarov et al , 2017; Johnsson et al , 2021).…”
Section: Theoretical Frame Of Referencementioning
confidence: 99%
See 2 more Smart Citations